A novel view of the manufacture of polyurethane-polyurea aqueous dispersions - Fernandes, Isabel P. (2008)
Over the past few decades, polyurethane-polyurea aqueous dispersions (PUDs) have developed a solid reputation for high performance applications, particularly in the field of adhesives and coatings. PUDs are mostly environmentally compatible products; they are totally devoid or contain only low amounts of volatile organic compounds (VOC). This is an important feature in view of the present environmental policies where governments and internal agencies are placing emphasis on developing sustainable processes, improving work conditions and reducing emissions of toxic and polluting substances into the atmosphere. Moreover, polyurethanes are known as “tailor-made” products with properties resulting from a wide diversity of raw-materials which can be combined in different ways during the synthesis. In recent years, our research group has been involved in the development of polyurethanepolyurea aqueous dispersions for various applications. With this work we intend to review this theme and describe the most recent developments. Characterization of industrial dispersions will be presented and examples of synthesis will be described.